Being Muslim today : reclaiming the faith from orthodoxy and islamophobia - Qureshi, Saqib Iqbal (Rowman & Littlefield, 2024)
"In Being Muslim Today, author Dr. Saqib Qureshi silences the noise that obscures the message of Islam. He provides a compelling presentation of the faith's beginnings, its evolution throughout the last 1,400 years, and its relevance today. He simplifies complicated academic debates and reveals the heart and soul of a growing faith tradition"--